Some theoretical and experimental aspect of magnetoresistance - Shaari, Abdul Halim; Abbas, Zulkifly; Wan Yusoff, Wan Daud; Saion, Elias; Khalid, Kaida; Lim, Kean Pah (Universiti Putra Malaysia Press, 2005)
Magnetoresistance (MR) is an effect in which the resistance of magnetic materials, varies as a function of applied magnetic fields. Giant magnetoresistance (GMR) was first observed in Fe/Cr multilayers. GMR is also found in magnetic granular thin films such as NiFeCo-Ag and Co-Ag. GMR mainly due to the spin dependent scattering of conduction electrons, which occurs in or within interface of magnetic particles. The resistance of these material drops significantly when these randomly oriented magnetic moments of the magnetic granules are aligned by external magnetic fields. Manganites oxide show a wide variety of interesting phenomena, most spectacular among them being the colossal magnetoresistance (CMR). The physical mechanism of existence in this huge magnetoresistance has been explained by double exchange interaction between mixed Mn3+ and Mn4+ ions, strong electron-phonon coupling (Jahn Teller distortion) and the charge ordering effect. When the local spins are aligned with direction of the applied magnetic field, double exchange interactions is enhanced and thus charge carries scattering is reduced.these give rise to the MR effect. In long- range ferromagnetism, the ferromagnetic ordering destroyed the localized spin Doping at La sites with other element can disturbed the double exchange mechanism by canting the Mn-O-Mn bond angle. At low field (about 0.1T), the gradient of (La1-xNdx)0.67Ba0.33MnO3 is 120% MR/Tesla. This value is very sensitive for low field application. For high field, the field gradient of is about 18% MR/Tesla. (La1-xNdx)0.67Ba0.33MnO3 phase transition temperature (Tp) shift to lower temperature when the doping concentration increases. These could be due to the breaking of the long range magnetic ordering along the Mn3+ - O - Mn4+ bonding. At low field (about 0.1T), the gradient of La0.67Ca0.33(Mn1-xPrx)O3 is 200%MR/Tesla. For high field, the field gradient of is about 24% MR/Tesla. However, at low concentration (0.03≤x≤0.1), a linear relationship between MR% and applied field with a gradient of about 20% MT/Tesla is observed.